2009
DOI: 10.2478/v10085-009-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Cenozoic paleoceanographic record in the Central Arctic Ocean: IODP Expedition 302 Synthesis

Abstract: Abstract:The Arctic Coring Expedition (ACEX) proved to be one of the most transformational missions in almost 40 year of scientific ocean drilling. ACEX recovered the first Cenozoic sedimentary sequence from the Arctic Ocean and extended earlier piston core records from ∼1.5 Ma back to ∼56 Ma. The results have had a major impact in paleoceanography even though the recovered sediments represents only 29% of Cenozoic time. The missing time intervals were primarily the result of two unexpected hiatuses. This impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 93 publications
(184 reference statements)
3
40
0
Order By: Relevance
“…It was only in 2004, when the Integrated Ocean Drilling Program (IODP) Expedition 302, the Arctic Coring Expedition (ACEX), retrieved the first long drill core from the central Arctic Ocean, that proposed tectonic models with palaeoceanographic implications could be compared with geological ground truth ). The 428 m long sediment record retrieved from the Lomonosov Ridge unveiled a range of novel results (e.g., Brinkhuis et al 2006;Moran et al 2006;Pagani et al 2006;Jakobsson et al 2007;Haley et al 2008;Backman & Moran 2009). One of these results suggests that the Arctic Ocean transformed from a poorly oxygenated ''lake stage'' to a fully oxygenated ''ocean stage'' during late early Miocene (17.5 Mya; Jakobsson et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…It was only in 2004, when the Integrated Ocean Drilling Program (IODP) Expedition 302, the Arctic Coring Expedition (ACEX), retrieved the first long drill core from the central Arctic Ocean, that proposed tectonic models with palaeoceanographic implications could be compared with geological ground truth ). The 428 m long sediment record retrieved from the Lomonosov Ridge unveiled a range of novel results (e.g., Brinkhuis et al 2006;Moran et al 2006;Pagani et al 2006;Jakobsson et al 2007;Haley et al 2008;Backman & Moran 2009). One of these results suggests that the Arctic Ocean transformed from a poorly oxygenated ''lake stage'' to a fully oxygenated ''ocean stage'' during late early Miocene (17.5 Mya; Jakobsson et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…The Integrated Ocean Drilling Program (IODP) Arctic Coring Expedition (ACEX), drilled a 428 m long sediment record from the Lomonosov Ridge in the central Arctic Ocean (Backman and Moran, 2009) (Fig. 1).…”
Section: Arctic Ocean Sea Icementioning
confidence: 99%
“…Ryan et al, 2009). Observed sulfatemethane transitions during the MITAS 1 expedition shown in black diamonds (Coffin et al, 2013) and Arctic Coring Expedition (ACEX) shown as red squares (Backman and Moran, 2009). …”
Section: East Siberian Margin Geologymentioning
confidence: 99%
“…So far, no deep drilling has occurred along SNESS. However, the 2004 Arctic Coring Expedition (ACEX; Backman et al, 2009) drilled and cored the central Lomonosov Ridge (Fig. 1).…”
Section: Current Speculation On Gas Hydrates In the Arcticmentioning
confidence: 99%
See 1 more Smart Citation